Debt Management and Financial Analysis System Programme Annual Report 2023 - UN Trade; Development (United Nations, 2024)
This annual report describes the activities, achievements and financial situation of the DMFAS Programme of the United Nations Conference on Trade and Development (UNCTAD) at the end of 2023. It is intended for the Programme’s donors, development partners and beneficiary countries, and for all those interested in debt and development issues.